FEM modeling based on molecular results for PE/SWCNT nanocomposites - M. Fattahi, A.; Roozpeikar, S.; A. Ahmed, N. (International Journal of Engineering and Technology, 2018)
This study aimed to evaluate the mechanical properties of single walled carbon nanotube (SWCNT) reinforced composites using 3-D representative volume element (RVE). Then, RVE was created by finite element method using ABAQUS software. By using the results of atomic modeling, fiber and matrix interface properties were extracted and then a model for predicting the elastic modulus of nanocomposites was presented. Also, the longitudinal elastic module of Polyethylene/ CNT nanocomposite was computed and compared with experimental results. Load transfer conditions between CNTs and matrix were modeled using a separated interfacial region. Numerical examples using FEM were presented. Based on the modeling results, the increase of weight fraction of nanotubes led to the increase of equal elastic modulus of nanocomposite. By increasing the volume fraction of CNTs in the experiments, the dispersion of particles was much more difficult and the empirical results of elastic modulus were lower than those predicted by finite element software.Â
Keywords: FEM; CNT; Elastic Modulus; Continuum Mechanic Model; RVE.